Tuberculosis of Calcaneus – A Case Report and Review of Literature - Poudel, Arjun; Poudel, Pranodan; Chand, Birendra Bahadur; Banskota, Bibek; Banskota, Ashok Kumar (Nepal Orthopaedic Association Journal, 2024)
Osteoarticular tuberculosis (TB) constitutes 1-3 % of cases of which about 10% affect the foot and ankle. In foot TB, the calcaneus is the most commonly affected bone. TB calcaneum is a rare entity and a high index of clinical suspicion along with imaging studies helps in diagnosis. Thorough debridement of the lesion along with chemotherapy for adequate duration helps in the complete resolution of infection with good functional results.